Peroxisome Proliferator-Activated Receptors in Lung Cancer - Venkateshwar G. Keshamouni; ShouWei Han; Jesse Roman (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors belonging to the nuclear hormone receptor superfamily. Their discovery in the 1990s provided insights into the cellular mechanisms involved in the control of energy homeostasis; the regulation of cell differentiation, proliferation, and apoptosis; and the modulation of important biological and pathological processes related to inflammation, among others. Since then, PPARs have become an exciting therapeutic target for several diseases. PPARs are expressed by many tumors including lung carcinoma cells, and their function has been linked to the process of carcinogenesis in lung. Consequently, intense research is being conducted in this area with the hope of discovering new PPAR-related therapeutic targets for the treatment of lung cancer. This review summarizes the research being conducted in this area and focuses on the mechanisms by which PPARs are believed to affect lung tumor cell biology.